Teacher education journal - Salandanan, Gloria G. (Quezon City, Philippines : Katha Publishing Co, Inc., 2001)
The Teacher Educational Journal represents my humble attempt to translate into imprint some of my thoughts that were part of my formal lectures, papers read, articles written and informal conversations with my colleagues during my eventful years at the pioneer teacher training institution, in the Philippine Normal University.
I. On teacher education -- II. On continuing professional teacher education -- III. On the teacher -- IV. On teaching and learning -- V. On teaching approaches -- VI. On assessment -- VII. On developing instructional materials.
Includes bibliographical references.
Keywords: EDUCATION